2016
DOI: 10.1074/jbc.m115.710947
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Dysfunction Caused by Cellular Accumulation of Silica Nanoparticles

Abstract: Nanoparticles (NPs) are widely used as components of drugs or cosmetics and hold great promise for biomedicine, yet their effects on cell physiology remain poorly understood. Here we demonstrate that clathrin-independent dynamin 2-mediated caveolar uptake of surface-functionalized silica nanoparticles (SiNPs) impairs cell viability due to lysosomal dysfunction. We show that internalized SiNPs accumulate in lysosomes resulting in inhibition of autophagy-mediated protein turnover and impaired degradation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 35 publications
8
50
0
Order By: Relevance
“…SiNPs have been shown to induce autophagy in various cell lines, such as HCT-116 human colon cancer cells, HepG2 human hepatoma cells, HUVECs, and RAW 264.7 murine macrophage cells [3,[19][20][21]. Moreover, our group and others have also reported that SiNPs induce autophagy dysfunction via lysosomal impairment and inhibition of autophagosome degradation [5,22]. Based on the aforementioned clues, we speculated that SiNPinduced autophagy dysfunction occurs via 2 mechanisms: first, through autophagy induction and enhanced autophagosome synthesis, and second, by autophagic degradation blockage.…”
Section: Introductionmentioning
confidence: 76%
“…SiNPs have been shown to induce autophagy in various cell lines, such as HCT-116 human colon cancer cells, HepG2 human hepatoma cells, HUVECs, and RAW 264.7 murine macrophage cells [3,[19][20][21]. Moreover, our group and others have also reported that SiNPs induce autophagy dysfunction via lysosomal impairment and inhibition of autophagosome degradation [5,22]. Based on the aforementioned clues, we speculated that SiNPinduced autophagy dysfunction occurs via 2 mechanisms: first, through autophagy induction and enhanced autophagosome synthesis, and second, by autophagic degradation blockage.…”
Section: Introductionmentioning
confidence: 76%
“…Lysosome is one of the major intracellular storage sites for SiNPs that enter into cells. 58 SiNPs accumulation in lysosomes has been suggested as a mechanism of cytotoxicity in lung epithelial cells, and its overload leading to delayed clearance and particle persistence can negatively impact lysosome function. 59 It has been reported that internalized SiNPs could cause destabilization of lysosomes and permeabilization of lysosome membranes, 60 resulting in ROS generation, cytosolic acidification, and eventually cellular death.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes play an important role in cell physiology, including in the degradation of exogenous elements or of endogenous damaged organelles, as well as in nutrient signaling and regulation of cell growth. 19 The presence of a large number of secondary lysosomes may indicate the unstable status of the tissues. Previous studies have shown that nanoparticles can penetrate organs following ingestion, injection, skin application, or inhalation through systemic circulation.…”
Section: Discussionmentioning
confidence: 99%